Determination of phenolic compounds and evaluation of antioxidant capacity of two grapes residues (Vitis vinifera) of varieties dried: Quebranta (red) and Torontel (white) - Solari-Godiño, Armando (2017)
The determination of phenolic compounds and antioxidant activity of grape pomace (Vitis vinifera) of two varieties: Quebranta (red) and Torontel (white) using two drying methods: freeze drying and cool air-drying was evaluated, using methods to preserve and maintain bioactive compounds like polyphenols and their antioxidant capacity, these are DPPH and FRAP assays. In general, according to solvent extraction for both grape pomace varieties using the two drying methods, there were obtained high contents of extractable, hydrolysable and condensed tannins polyphenols and therefore exhibited high antioxidants capacities. However, Torontel grape pomace variety obtained by cool air-drying was better in extractable polyphenols, DPPH· and FRAP assays, than those obtained by freeze drying, being 6,095.36 ± 0.58 mg GAE/100 g pomace, 4,042.57 ± 27.80 mg pomace/g DPPH·, 390.23 ± 7,14 µM Trolox/g pomace, respectively. For Quebranta grape pomace variety obtained by cool air-drying and freeze drying; the extractable polyphenols, DPPH· and FRAP assays did not showed differences (p < 0.05). On the other hand, there were no differences (p < 0.05) between contents of hydrolyzable and condensed tannins in polyphenols for both drying methods, however the antioxidant capacity by DPPH· and FRAP assays showed differences (p < 0.05). Finally, this study demonstrated that cool air-drying method preserves the components of grape pomace, being a favorable advantage to optimize costs and drying times, in comparison to Freeze drying, and the first one also takes advantage to formulate and elaborate new products to be incorporated in several foods as a functional ingredient.